Study the Use of Activated Carbon and Bone Char on the Performance of Gravity Sand-Bag Water Filter - Eric Fung (MDPI AG, 2021)
In this study, granulated activated charcoal (GAC) and bio charcoal (BC) is used as a filler in P3 biosand bag filter to study their filtration performance against a range of fluoride impurities from 1–1400 mg/L. A set of experiments are done to analyze the filtration efficiency of the sandbag filter against fluoride impurities after incorporating different amounts (e.g., 0.2, 2 kg) and a combination of GAC and BC. A combination of filler GAC and BC (1 kg each) have exhibited excellent results with 100% fluoride removal efficiency against 5 mg/L fluoride impurities for an entire experimental time of 165 min. It is because of the synergetic effect of adsorption caused by the high surface area (739 m2/g) of GAC and hydroxyapatite groups in BC. The data from remediation experiments using individual GAC and BC are fitted into the Langmuir and Freundlich Isotherm Models to check their adsorption mechanism and determine GAC and BC’s maximum adsorption capacity (Qm). The remediation data for both GAC and BC have shown the better fitting to the Langmuir Isotherm Model with a high R2 value of 0.994 and 0.970, respectively, showing the excellent conformity with monolayer adsorption. While the GAC and BC have presented negative Kf values of −1.08 and −0.72, respectively, for Freundlich Model, showing the non-conformity to multilayer adsorption. The Qm values obtained from Langmuir Model for GAC is 6.23 mg/g, and for BC, it is 9.13 mg/g. The pH study on adsorption efficiency of individual GAC and BC against 5 mg/L of fluoride impurities indicates the decrease in removal efficiency with an increase in pH from 3 to 9. For example, BC has shown removal efficiency of 99.8% at pH 3 and 99.5% at pH 9, while GAC has exhibited removal efficiency of 96.1% at pH 3 and 95.9% at pH 9. Importantly, this study presents the significance of the synergetic application of GAC and BC in the filters, where GAC and BC are different in their origin, functionalities, and surface characteristics.